Storm Prey : Lucas Davenport #20 - Sandford, John, 1944 Feb. 23- (New York : G. P. Putnam's Sons, 2010)
For 12 years, Pendergast has believed that the death of his wife, Helen, in the jaws of a ferocious red-maned lion in Zambia was just a tragedy, but his chance examination of the gun she carried on the fateful day reveals that someone loaded it with blanks. Pendergast drags his longtime NYPD ally, Lt. Vincent D'Agosta, into a leave of absence that includes travel to Africa as well as the American South. The motive for Helen's murder appears to be linked to her fascination with John James Audubon and her quest for a mysterious lost Audubon painting.
Keywords: Davenport, Lucas (Fictitious character) -- Fiction; Police -- Minnesota -- Minneapolis -- Fiction; Minneapolis (Minn.) -- Fiction; Mystery fiction